2008
DOI: 10.1016/j.virol.2008.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell leukemia virus type 1 Tax modulates interferon-α signal transduction through competitive usage of the coactivator CBP/p300

Abstract: We describe here Tax protein of human T-cell leukemia virus type 1 (HTLV-1) as an interferon (IFN)-alpha antagonist counteracting the transactivation function of IFN-stimulated gene factor 3 (ISGF3). Co-expression of Tax, but not the Tax mutant unable to bind to CBP, significantly inhibited the reporter gene expression directed by IFN-stimulated regulatory elements, despite that the formation of DNA-binding ISGF3 complex was unaffected. Gene activation induced by STAT2 transcription domain was also inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…For example, our data indicate that, at higher concentrations, Tax also inhibits activation of type I IFN by activated IRF3/7, presumably by competition for transcription cofactors such as CBP/p300 (56).…”
Section: Discussionmentioning
confidence: 78%
“…For example, our data indicate that, at higher concentrations, Tax also inhibits activation of type I IFN by activated IRF3/7, presumably by competition for transcription cofactors such as CBP/p300 (56).…”
Section: Discussionmentioning
confidence: 78%
“…Earlier studies indicated suppression of HTLV-1 expression by type I IFNs in vitro (25), and favorable clinical effects of a combination therapy of IFN-␣ and zidovudine for ATL (6). A recent report indicated that overexpression of HTLV-1 Tax inhibited the effects of type I IFN signals by competing with CBP/p300 (36). This may partly explain why the suppressive effect of stromal cells was weak on MT-2 cells (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…HTLV-1 blocked IFN-␣-mediated induction of ISGs by antagonizing the phosphorylation of TYK2 and STAT2 (7); however, the viral protein responsible for the IFN inhibitory effect was not identified. Another study implicated HTLV-1 Tax as an inhibitor of IFN signaling via competition of Tax with STAT2 for the coactivators CBP/p300 (53). Taken together, it appears that HTLV-1, and possibly Tax, inhibits IFN signaling.…”
mentioning
confidence: 97%